2011
DOI: 10.4028/www.scientific.net/amr.368-373.2109
|View full text |Cite
|
Sign up to set email alerts
|

Subway Monitoring System Based on TM30 Georobot Research and Implementation

Abstract: This article describes the basic principles of TM30 Georobot and GeoCOM port, completed the structural design of subway monitoring system database; Based on development environment with Visual Basic 6.0, Monitoring data to achieve automated collection of subway, as well as real-time analysis of monitoring data, Among them, the data were analyzed using different wavelet analysis model. Finally the automatic system is provided with monitoring data acquisition, real-time analysis and pre-alarm function, and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…3. Liu Ran [20] synthesized BN-MgAlON composite powders by carbothermal reduction and nitridation from boron-rich slag and carbon black as raw materials. The experimental result showed that B 2 O 3 was trans-formed into BN, Al 2 O 3 and SiO 2 form MgAlON phase which could react with high purity nitrogen and holding time 8h at 1480℃.…”
Section: New Methodsmentioning
confidence: 99%
“…3. Liu Ran [20] synthesized BN-MgAlON composite powders by carbothermal reduction and nitridation from boron-rich slag and carbon black as raw materials. The experimental result showed that B 2 O 3 was trans-formed into BN, Al 2 O 3 and SiO 2 form MgAlON phase which could react with high purity nitrogen and holding time 8h at 1480℃.…”
Section: New Methodsmentioning
confidence: 99%
“…With the crowd, narrow space, lighting conditions and other complex influences in the subway environment, the existing imaging systems cannot fully make effects. The study of subway counterterrorism video surveillance intelligence analysis system mainly aims to the existing subway supervisory system in terms of the presence of anti-terrorism and counter-terrorism technical problems [3][4][5], such as low levels of artificial intelligence, cannot immediately suspicious circumstances. In complex environments such as many people, it is difficult for instant face image positioning, extraction, analysis and identification.…”
Section: Introductionmentioning
confidence: 99%